Increased blood pressure during the suggested immobilization test in Restless Legs Syndrome. Issue 4 (23rd October 2019) - Rassu, Anna Laura; Chenini, Sofiène; Barateau, Lucie; Lopez, Regis; Evangelista, Elisa; Guiraud, Lily; Jaussent, Isabelle; Dauvilliers, Yves
Abstract: Objective: To investigate the relationship between sensory discomfort/motor component and cardiovascular autonomic response by continuous beat-to-beat blood pressure monitoring (CBPM) during the suggested immobilization test (SIT) in patients with restless legs syndrome (RLS). Methods: Thirty-two drug-free patients with primary RLS (10 men; mean age 60.29 ± 10.81 years) and 17 healthy controls (2 men; mean age 58.82 ± 11.86 years) underwent a 1-hour SIT starting at 8 pm with concomitant CBPM to measure the heart rate (HR) and systolic/diastolic blood pressure (SBP, DBP). In all subjects, the presence of sensory discomfort and motor component during the SIT (S-SIT+ and M-SIT+, respectively) was quantified. Mixed regression models were used to compare the SBP, DBP, and HR profiles during the SIT by taking into account the repeated measures (6 time periods of 10 minutes). Results: In patients with S-SIT+ ( n = 17), SBP ( p < 0.0001), DBP ( p = 0.0007), and HR ( p = 0.03) increased during the SIT compared with other patients and controls. Seventeen patients had M-SIT+ (none among healthy controls). Classifying patients in 4 groups in function of the presence/absence of the SIT sensory and motor components revealed that SDB and DBP increased throughout the SIT in patients with S-SIT+, independently of the motor component ( p < 0.0001 and p = 0.0008 for SBD; p < 0.0001 and p = 0.01 for DBP in the S-SIT+/M-SIT − and S-SIT+/M-SIT+ groups, respectively). Conclusion: During the SIT, BP concomitantly increased only in patients with RLS and sensory discomfort, with or without motor component. This highlights the link between evening sensory RLS symptoms, autonomic activation, and potential long-term cardiovascular consequences.